(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
The susceptibility of railway operations to disruptions and its over-dependence on compliance to a schedule necessitates contingency measures to be put in place to manage such disruptions. The efficiency of a railway system has a lot to do with how robust such measures are. These disruptions are uncertain and as such, provided measures to counter them do not always agree with reality. The problem becomes more complicated when it occurs in real-time and at the station. To solve such problem, a complete resolution of all conflicting activities (train operations and maintenance tasks) must be carried out. These mutually exclusive activities compete for track allocation in the railway network. Existing solutions mainly focus on solving conflicts in train operations and neglect existing maintenance tasks. This research presents a MILP formulation of the problem and demonstrates how a disturbed train operations plan can be rescheduled while considering station infrastructure maintenance tasks. Four practical scenarios of this problem are presented and analyzed. Test results from real-life data demonstrate the efficacy of this formulation in handling various practical scenarios of the described problem within reasonable computational times.